Monte Carlo Simulation of Bony Heterogeneity Effects on Dose Profile for Small Irradiation Field in Radiotherapy - Cardoso, Simone C. (Public Library of Science, 2010)
In the radiotherapy treatment planning of a lesion located in the head region with small field radiation beams, the heterogeneity corrections play an important role. In this work, we investigated the influence of a bony heterogeneity on dose profile inside a soft tissue phantom containing a bony material. PDD curves were obtained by simulation using the Monte Carlo code EGSnrc and employing Eclipse® treatment planning system algorithms (Batho, Modified Batho, Equivalent TAR and Anisotropic Analytic Algorithm) for a 15 MV photon beam and field sizes of 2×2 and 10×10 cm(2). The Equivalent TAR method exhibited better agreement with Monte Carlo simulations for the 2×2 cm(2) field size. The magnitude of the effect on PDD due to the bony heterogeneity for 1×1, 2×2 and 10×10 cm(2) field sizes increases to 10, 5 and 3%, respectively.